Beat the Street in Reading A city-wide physical activity intervention to get a whole population active using RFID/NFC technology - Veronica Jean Reynolds (Frontiers Media S.A., 2015)
Introduction In Summer 2014 Intelligent Health delivered 'Beat the Street' in Reading with the aim to get a whole community more physically active. Beat the Street turns the town into a real life game where players register their walking and cycling journeys by tapping a smartcard on 220 RFID readers called 'Beat Boxes' placed on lampposts around the town. Players monitor their progress via a website where they can see their own and their team's progress, and the overall target. The project was re-commissioned in June 2015. Methods Participants were recruited through and via schools, receiving a smartcard for themselves and family members from their teacher and a map of Beat Box locations. Recruitment also took place from community groups, workplaces and GP surgeries. Participants who were not pre-registered through their school registered online. During the registration process they were able to pick a team for their points to be awarded to. 10 points were awarded for every valid journey between two Beat Boxes which were placed at key destinations across the town, approximately 0.5 miles apart. Points contributed to individual and team scores. During registration, participants completed a questionnaire which included a single item physical activity question.(i) Follow up surveys took place at the end of the game and 3 months later. Registration from the 2015 game were used to compare results between participants who took part in both years. The results were analysed by an independent team at The Evidence Centre. Results In 2014, 15,000 people in 50 teams walked and cycled 244,537 miles in 8 weeks. There were 8000 children and 7000 adults. 12% of adults had a long-term condition such as COPD, arthritis or diabetes. In 2015, the number of participants increased by 63% to 24,074. In 2015 they walked 303,000 miles. In 2014, 1051 completed the single item p.a. question both before and after the competition. There was a 10% increase (<0.05) in the number of people who reached the Government target of 150 mins/week and 14% reduction in those who did zero minutes of activity/week. 35% of people reported meeting the guidelines for levels of activity at the beginning compared with 45% at the end. 3 months later this was maintained at 53%. (>0.05). The changes remained when data from individuals was matched. 78% of people said Beat the Street helped them to walk more than usual and 70% said they continued to walk more after Beat the Street ended. 76% of people said they would try to continue the changes after the competition ended and 3 months later 75% said they continued to be more active. The main reason given for taking part was 'having fun' or 'keeping fit'. At the beginning of the game in 2015, 46% of those who had taken part before reported meeting 150 mins/week compared to 40% of people who had not taken part before. (>0.05) At the end of Beat the Street in 2015, the trends were even more positive. Both people participating for the first-time and those who had taken part before were more likely to be meeting the p.a. target at the end- but past participants had even greater gains than first-timers. Discussion and Conclusion Beat the Street may help people make some immediate changes to their p.a. levels. These changes may be sustained one year later. With repeated participation in Beat the Street, activity levels may increase even further. Further analysis is currently underway to explore walking speed, as an objective measure of fitness, in the 2015 cohort and sub-groups thereof, in particular the least active and those with a long term condition or in the older age categories. Since 2014,107,000 people have played Beat the Street across 11 projects. It is one of the initiatives being tested as part of the EU-funded SWTICH campaign to enhance active travel through technology and health messages. The cost per participant of Beat the Street in Reading was €8 and this means that for every €1 spent over two years there was a return of €21.48 for health, €5.21 for transport and €24.15 for economic productivity. This gives a total of €48 return for every €1 spent.(ii)